2006
DOI: 10.1002/cne.21049
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and morphological characterization of parvalbumin‐containing interneurons of the rat basolateral amygdala

Abstract: The basolateral amygdala (BLA) is critical for the generation of emotional behavior and the formation of emotional memory. Understanding the neuronal mechanisms that contribute to emotional information processing in the BLA will ultimately require knowledge of the anatomy and physiology of its constituent neurons. Two major cell classes exist in the BLA, pyramidal projection neurons and nonpyramidal interneurons. Although the properties of projection neurons have been studied in detail, little is known about t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
140
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 133 publications
(161 citation statements)
references
References 113 publications
21
140
0
Order By: Relevance
“…Although these cells were not identified according to the presence of calciumbinding proteins, their firing properties are in general similar to those of the cells we characterized as FS. A stuttering phenotype has also been previously reported in the BLA (Washburn and Moises, 1992) and neurons with similar properties have more recently been shown to express parvalbumin (Rainnie et al, 2006). In our sample, FS cells (75 of 158) ( Fig.…”
Section: Identification and Classification Of Pv؉ Interneuronssupporting
confidence: 86%
See 1 more Smart Citation
“…Although these cells were not identified according to the presence of calciumbinding proteins, their firing properties are in general similar to those of the cells we characterized as FS. A stuttering phenotype has also been previously reported in the BLA (Washburn and Moises, 1992) and neurons with similar properties have more recently been shown to express parvalbumin (Rainnie et al, 2006). In our sample, FS cells (75 of 158) ( Fig.…”
Section: Identification and Classification Of Pv؉ Interneuronssupporting
confidence: 86%
“…Of these, parvalbumin-containing (PVϩ) neurons form ϳ50% of the interneuronal population, showing extensive colocalization with calbindin (McDonald and Betette, 2001), but not expressing the other markers. Electrophysiological recordings from interneurons in the BLA both in vitro (Rainnie et al, 1993(Rainnie et al, , 2006Mahanty and Sah, 1998) and in vivo (Lang and Pare, 1998) have also revealed a diversity of firing properties. However, little is known about the identity of these interneurons or their connectivity.…”
Section: Introductionmentioning
confidence: 99%
“…11,12,28 A block of tissue containing the hippocampus was then mounted on the chuck of a Leica VTS-1000 vibrating microtome (Leica Microsystems Inc., Bannockburn, IL, USA), and 350 mm coronal slices were cut. Slices were then hemisected and transferred to a holding chamber containing ACSF KA at room temperature and gassed with a 95-5% oxygen/carbon dioxide mixture for 1 h before being placed in oxygenated control ACSF containing (in mM): NaCl (130), KCl (3.5), KH 2 PO 4 (1.1), MgCl 2 (1.3), CaCl 2 (2.5), NaHCO 3 (30) and glucose (10).…”
Section: Electrophysiologic Methodsmentioning
confidence: 99%
“…Cell-type-specific lentivirus in brain JP Chhatwal et al electrophysiologic properties of interneurons in the rat brain, [11][12][13] we explored the use of the CCK-GFP virus as a means to label cells for fluorescently guided electrophysiologic recording in vitro. Twelve days following in vivo infection, acute brain slices were prepared and electrophysiologic recordings were obtained from visually identified CCK-GFP-infected neurons of the rat hippocampus.…”
Section: Transgene Expression For Fluorescence-guided Electrophysiolomentioning
confidence: 99%
See 1 more Smart Citation